The Relationship Between Simultaneous Thinking and Performance Skills in Typography Technique Among Students of the Institute of Fine Arts (Journal of the College of Basic Education, 2025)
This study aims to examine the relationship between concurrent thinking and performance skills in typography technology among students of the Institute of Fine Arts. The descriptive correlational method was used, where the Concurrent Thinking Scale and the Performance Skills Evaluation Form were applied to a sample of students. The results revealed a statistically significant relationship between concurrent thinking and performance skills, indicating the impact of concurrent thinking on enhancing students’ skill efficiency in typographic design. The study recommends integrating educational strategies that foster concurrent thinking in typography curricula to develop students’ skills and improve the quality of performance output.